Swirls: A Platform for Enabling Multicluster and Multicloud Execution of Parallel Programs - Carvalho Junior, Francisco Heron de; Dantas, Allberson Bruno de Oliveira; Sales, Claro Henrique Silva (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2021)
Swirls is a general purpose application for interactive building, deploying, and execution of message-passing parallel programs that address multicluster and multicloud requirements. It is implemented on HPC Shelf, a cloud-based platform for providing HPC services. Swirls enables the communication between MPI programs written in C#, C, C++, and Python across one or more clusters, either on-premise or cloud-based ones. At the current implementation status, The users of Swirls may use clusters formed by virtual machines over Amazon Elastic Compute Cloud (EC2) and Google Cloud Platform (GCP).